A reflection on the polis for pigs - Socrates' true and healthy polis - Christianson, Arnold Lewis (My University, 2015)
Plato in his dialogue the Republic designs an ideal polis, the Kallipolis, seeking ‗justice, our good and the knowledge of the good required for understanding and bringing justice, happiness and good government into our lives and society‘ (Santas 2010, p.7). The first step in the Kallipolis‘ development is a polis without formal government whose citizens live a modest, stable, sustainable lifestyle. Disparaged by Glaucon as a polis for pigs, Socrates‘ incongruous rejoinder is ‗the true polis… is the one we‘ve described, the healthy one, as it were‘ (Rep. 372e). Contemporary commentators are critical of this polis, questioning its role in the Republic. In trying to understand the polis for pigs, and Socrates‘ praise thereof, I posit it is a village, and consider it has virtue, is good and its citizens are happy. However, despite being true and healthy, it is not the best or an ideal polis, but it is crucial to the development of the Kallipolis.
Thesis (M.A. (Applied Ethics for Professionals))--University of the Witwatersrand, Faculty of Humanities, School of Social Sciences, 2015.
Keywords: Ethics; Plato; Socrates; Plato's Republic